(untitled) (Research, Society and Development, 2022)
Ketosis in dairy cattle is a metabolic disorder caused by negative energy balance in the postpartum period. It is an attempt to supply the lack of free glucose using the reserve fat to produce ketone bodies (CC), which are acetone, aceto acetate and β-hydroxybutyrate (BHB). Ketosis causes problems due to the accumulation of CC, lack of appetite and consequent loss of body condition score and possible secondary illness due to decreased food intake. Early detection of changes in the health of the dairy cow allows interventions to be taken before the animals’ production levels, or even their survival, are at risk. The objective of this work was to evaluate the feasibility of using a rapid test in milk for BHB in postpartum dairy cows in the municipality of Carambeí-PR. Fifty Holstein dairy cows were evaluated in the postpartum period. Blood and milk samples were taken simultaneously. The reagent strip was used in the Health Mate BHB Milk (DFI), and in its control, a rapid test device for BHB in Ketovet blood was used. The tests were repeated at 4, 7 and 14 days postpartum, totaling 150 tests. There was a positive correlation between the rapid test performed with the DFI reagent strip and the blood test. At 7 to 14 days they are the most indicated for the diagnosis of ketosis, using the reagent strip in the milk, and on the 14th day there is the strongest correlation of 78% between the tests, and with a variation of 2% in the indication or not from treatment. The reagent strip has the advantages of performing the diagnosis quickly and at a low cost in the field, making it possible to avoid health and financial losses.